Arabic For Specific Purpose And Systematic Literature Review On The Design Of Islamic Tourism Mobile Application - Mohammad Najib Jaffar; Azman Ab Rahman; Mohd Nizwan Musling; Nurkhamimi Zainuddin; Siti Rosilawati Ramlan; Mohammad Imran Ahmad; Ghazali Zainuddin; Muhammad Sabri Sahrir (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Tourism is now a growing trend in the age of technology, whereby all information related to tourism can be easily accessed through smartphones. Malaysia is no exception to being a focused country as a popular Islamic tourism destination. However, there was insufficient tourism-related information, especially on Muslim tourists via smartphone. Hence the present article conducted a systematic literature review on the design and development of Islamic tourism applications via smartphones focusing on the Android platform. This study selected related articles using three databases: EBSCOhost, Mendeley, and Google Scholar. Based on the thematic analysis, this review has five main themes, namely 1) Islamic tourism; 2) technology; 3) mobile application; 4) barriers; and 5) management. The findings prompted the design and development of a smartphone application that addresses all of the needs of tourists, mainly Muslim tourists. This study also contributes to the use of technology and mobile application in teaching and learning Arabic for specific purposes such as tourism.